A cross sectional study on appropriate use of face mask among adults seeking primary health care services in Chennai - Dharmalingam, Priyadharshini; J., Princy Felicia; Murugesan, Vidhya; Balasubramanian, Sindhubala (International Journal Of Community Medicine And Public Health, 2021)
Background: The WHO has recommended face mask use during COVID-19 pandemic for all people in all public settings and situations compromising the social distancing. So, face mask use, hand hygiene and social distancing are the preventive measures followed by many countries against this pandemic. But still inappropriate use of masks might lead to failure of these preventive measures against COVID. So, this study was done to determine the prevalence and determinants associated with knowledge and practices of the appropriate use of face masks among patients attending primary health care services in a slum of Chennai. Methods: A cross-sectional study was done among patients attending urban primary health centre for non-respiratory complaints. A pretested semi-structured questionnaire was used to collect information from the participants. For assessment of practice, direct observation on the use of a face mask was done. Data were entered in Excel and analysed using SPSS 23.0 software. The Chi-square test was used to analyse the determinants. Results: Only 10% had the knowledge and none had an appropriate practice of face mask use. 85.5% used face mask with the majority being fabric mask users. The male, age >40 years and low SES had significantly poor knowledge on the appropriate use of face mask. Conclusions: The high prevalence of inappropriate knowledge and practice of use of face masks implies that along with awareness of mask use, behavioral change on appropriate face mask practices is needed.